Pola Asuh Otoritatif Guru Terhadap Penerapan Nilai-Nilai Pendidikan Karakter Peserta Didik PAUD - Rudie, Rudie; Sartica, Dwi; Purwanti, Natali (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This study aimed to determine: (i) the correlation between the influence of authoritative parenting patterns of teachers (variable X) on the implementation of educational values ​​for PAUD students (variable Y), (ii) the relationship between the two variables, and (iii) how much contribution variable X made to variable Y. This type of research was quantitative correlation, with a population of 155 PAUD teachers and a sample of 74 PAUD teachers. Data collection techniques were observation, documentation, interviews and questionnaires. The data analysis technique used the Pearson Product Moment correlation technique and the t-test technique. Thus, it could be concluded that the authoritative parenting pattern of teachers had a significant influence on the implementation of character education values ​​for PAUD students and the contribution of this influence is 74.7% while 25.3% is influenced by other parenting patterns that are not included in this study. This is in accordance with the results of observations made by researchers that PAUD students prefer to obey or follow orders or instructions given by teachers rather than their own mothers at home.